A Note on Continuity of Solution Set for Parametric Weak Vector Equilibrium Problems - Pakkapon Preechasilp; Rabian Wangkeeree (Abstract and Applied Analysis)
We consider the parametric weak vector equilibrium problem. By using a weaker assumption of Peng and Chang (2014), the sufficient conditions for continuity of the solution mappings to a parametric weak vector equilibrium problem are established. Examples are provided to illustrate the essentialness of imposed assumptions. As advantages of the results, we derive the continuity of solution mappings for vector optimization problems.